Composition and properties of drilling and completion fluids - Caenn, Ryen.; Darley, H. C. H. (Henry C. H.), 1911-; Gray, George Robert, 1907-; Gray, George Robert, 1907- (Amsterdam ; Boston, MA : Gulf Professional Pub., 2011)
The petroleum industry in general has been dominated by engineers and production specialists. The upstream segment of the industry is dominated by drilling/completion engineers. This text incorporates information on technology, economic, and political issues that have impacted the use of fluids to drill and complete oil and gas wells.
Rev. ed. of: Composition and properties of drilling and completion fluids / H.C.H. Darley, George R. Gray.
Includes bibliographical references and indexes.
Keywords: Drilling muds; Completion fluids